Sirt6 Deacetylase: A Potential Key Regulator in the Prevention of Obesity, Diabetes and Neurodegenerative Disease - Raj, Swapnil; Dsouza, Liston Augustine; Singh, Shailendra Pratap; Kanwal, Abhinav (Frontiers in Pharmacology, 2020)
Sirtuins, NAD + dependent proteins belonging to class III histone deacetylases, are involved in regulating numerous cellular processes including cellular stress, insulin resistance, inflammation, mitochondrial biogenesis, chromatin silencing, cell cycle regulation, transcription, and apoptosis. Of the seven mammalian sirtuins present in humans, Sirt6 is an essential nuclear sirtuin. Until recently, Sirt6 was thought to regulate chromatin silencing, but new research indicates its role in aging, diabetes, cardiovascular disease, lipid metabolism, neurodegenerative diseases, and cancer. Various murine models demonstrate that Sirt6 activation is beneficial in alleviating many disease conditions and increasing lifespan, showing that Sirt6 is a critical therapeutic target in the treatment of various disease conditions in humans. Sirt6 also regulates the pathogenesis of multiple diseases by acting on histone proteins and non-histone proteins. Endogenous and non-endogenous modulators regulate both activation and inhibition of Sirt6. Few Sirt6 specific non-endogenous modulators have been identified. Hence the identification of Sirt6 specific modulators may have potential therapeutic roles in the diseases described above. In this review, we describe the development of Sirt6, the role it plays in the human condition, the functional role and therapeutic importance in disease processes, and specific modulators and molecular mechanism of Sirt6 in the regulation of metabolic homeostasis, cardiovascular disease, aging, and neurodegenerative disease.